"Tell Me Something Good": Testing the Longitudinal Effects of Constructive News Using the Google Assistant. (March 2020) - McIntyre, Karen
Americans say that reading, watching, or listening to the news is one of their leading causes of stress. And indeed, research has shown that negative news can negatively impact people's attitudes, behaviors, and mental health. To combat the unwelcome effects of negative news, some have suggested that reporters practice more constructive or solution-oriented journalism by reporting stories that highlight societal progress. Drawing on cognitive appraisal theory and the broaden-and-build theory of positive emotions, this study tested the impact of constructive news. In a mixed-design quasi-experiment, participants received access to a Google Assistant feature in which they could prompt the assistant to summarize a constructive news story. After 2 weeks, those who used the feature were more likely, between pretest and posttest, than those who did not to feel positive while consuming traditional news, suggesting constructive news could mitigate the effects of more typical, negative news.